PERAN K.H. ZEN MASRUR DALAM SISTEM PENDIDIKAN DI PONDOK PESANTREN AL KAMAL BLITAR 1969– 1999 - Gurung, Sitbri (Historia Islamica: Journal of Islamic History and Civilization, 2025)
ABSTRACT-This research This research describes the role of K.H. Zen Masrur in the education system at the Al Kamal Islamic Boarding School 1969-1999. Kiai Zen Masrur is one of the PPTA kiai and caregivers involved in the development of PPTA. Kiai Zen Masrur's role is not only to teach at Islamic boarding schools and formal schools, but also to be a community figure who is willing to consider input from the Kunir Village community. The aim of this research is First, to find out the learning system at the Al Kamal Integrated Islamic Boarding School from what was initially sorogan and bandungan to become pure salafi and then changed to integrated. Second, to find out the biography and contributions of Kiai Zen Masrur when he took part in the education system at the Al Kamal Integrated Islamic Boarding School. Apart from teaching, Kiai Zen Masrur is also a community figure in Kunir Village. The method used in this research uses a historical research method which consists of four stages, namely heuristics (data collection), verification (source criticism), interpretation (interpretation of data), and finally historiography (writing history). The results of this research show that Kiai Zen Masrur has the following roles: First, in education at the Al Kamal Integrated Islamic Boarding School as a caregiver and teaching Islamic religious knowledge. Second, play a role in teaching at the formal school belonging to the Al Kamal Integrated Islamic Boarding School. Third, play a role in the socio-religious field, such as carrying out da'wah and accommodating aspirations or suggestions from the people of Kunir Village. Keywords: Al Kamal, Kiai Zen Masrur, Education, Integrated.